Dividend Policy: Are Agency Costs and R&D Investments Important? - Arie Widya Kafitasari; Annisa Ilma Hartikasari; Azmi Fitriati; Bima Cinintya Pratama (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2024)
Dividend policy is an essential component that cannot be separated from a company's profits. In this research, the dividend policy of companies included in the IDX High Dividend 20 stock index will be tested by paying attention to the agency cost factor, which is proxied by free cash flow, ownership dispersion, insider ownership, and asset growth as well as the level of R&D investment carried out. Between 2018 and 2022, 31 companies joined the stock index with the highest dividend yield. This research shows that free cash flow significantly and positively affects dividend policy, and insider ownership significantly and negatively affects dividend policy. Meanwhile, the variables dispersion of ownership, asset growth, and R&D investment do not affect dividend policy. Some of the applications that companies can implement are being able to increase the number of dividends that will be announced by increasing the amount of free cash flow available, considering in detail the potential interests of insider ownership to decide on an appropriate policy, and being able to use internal funds wisely for good purposes. Distribute dividends or make R&D investments.